2009
DOI: 10.1203/pdr.0b013e3181973b22
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Neuroendocrine Cell-Secreted Factors May Alter Fetal Lung Liquid Clearance

Abstract: ABSTRACT:The neuroendocrine system is most active at birth and may play a role in the transition from fetal to postnatal life, in particular in the lungs' transition from fluid secretion to fluid absorption. Pulmonary neuroendocrine cells do release dopamine (DA), serotonin, and gastrin-releasing peptide but their effects on lung ion and fluid transport are poorly understood. Therefore, we studied their effects on fetal distal lung explants and primary cultures of fetal distal lung epithelium (FDLE). We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies using the thiourea-induced lung injury model have shown histologically that there was significant edema accumulation in the alveolus and in the interstitial space [17,19]. This accumulation of liquid in the lung could trigger physiological responses known to stimulate lung neuroendocrine cells [26], which can release amines, such as serotonin [26,27] or dopamine [28], which are known to stimulate lung liquid clearance [28][29][30][31]. Future experiments are needed to explore this hypothesis.…”
Section: Figurementioning
confidence: 96%
“…Previous studies using the thiourea-induced lung injury model have shown histologically that there was significant edema accumulation in the alveolus and in the interstitial space [17,19]. This accumulation of liquid in the lung could trigger physiological responses known to stimulate lung neuroendocrine cells [26], which can release amines, such as serotonin [26,27] or dopamine [28], which are known to stimulate lung liquid clearance [28][29][30][31]. Future experiments are needed to explore this hypothesis.…”
Section: Figurementioning
confidence: 96%